Individual Investment: How Financial Literacy and Self-Monitoring Drive Investment Decisions - Bustani Bustani (Komunitas Dosen Indonesia, 2024)
Investment decision-making has undergone significant evolution with a focus on financial literacy and self-monitoring in the modern context. From early theories rooted in rationality and psychology, such as utility theory and consumer behavior theory, to a concentration on grasping financial concepts like inflation and risk, this journey is characterized by an increasing awareness of individual financial competence. This study explores the crucial roles of financial literacy and self-monitoring in shaping investment decisions in Banjarmasin, a city experiencing rapid economic growth in Indonesia. Using the theoretical framework of Behavioral Finance, the research identifies that individuals with higher financial literacy tend to make more informed, goal-oriented investment decisions while self-monitoring influences investment behavior towards more disciplined and adaptive choices. Employing a quantitative approach based on Partial Least Squares Structural Equation Modeling (PLS-SEM), data was collected through surveys using questionnaires developed from pertinent literature and validated instruments involving 100 individual investors in Banjarmasin who participated voluntarily as respondents. The study's findings reveal that financial literacy and self-monitoring significantly impact individual investment decisions, offering critical insights for developing more effective financial education and supportive investment policies applicable in Banjarmasin and globally. Despite limitations in generalizing to a specific sample, this research contributes to a literature that remains sparse in the context of local investors, advocating for further longitudinal, comparative, and technologically enhanced studies in financial literacy and investment decision-making.